Effects of Selected Phytochemicals from Malaysian Plants on Cellular Models of Inflammation - Ahmad, Syahida (2006)
Inflammatory diseases of unknown causes are difficult to treat, although non-steroidal anti-inflammatory drugs (NSAIDs) are anticipated to be useful drugs. It was believed that bioactive compounds isolated from plants might have potential anti-inflammatory properties without any side effects. Therefore, the main objectives of this study were to evaluate the effects of selected phytochemicals from Malaysian plants on the production of main inflammatory mediators and to study their mechanism of action in cellular models of inflammation. Through the preliminary study, four out of the 32 phytochemicals tested were selected. They were atrovirinone, cardamonin, flavokawain B and zerumbone, which were isolated from Garcinia atroviridis, Alpinia rafflesiana, Alpinia zerumbet and Zingiber zerumbet respectively. All four compounds inhibited the release of interferon-γ (IFN-γ)/ lipopolysaccharide (LPS)-induced nitric oxide (NO) in macrophages cell line (RAW 264.7) without any cytotoxicity effect, which was measured using the Griess assay. In order to determine the mechanism of action of these compounds, further study on the production of main inflammatory mediators were conducted using several bioassays, namely oxidative stress assay, prostaglandin E2 (PGE2) and thromboxane B2 (TxB2) radioimmunoassay, and cytokines (tumour necrosis factor-α; TNF-α, interleukin (IL)-1β, IL-6 and IL-10) immunoassays. For the regulation and mechanism studies, the four compounds were tested on the main signaling pathways, which were the extracellular signal-regulated kinases (ERKs) and p38 MAPK pathways. The results showed that atrovirinone, cardamonin, flavokawin B and zerumbone significantly suppressed IFN-γ/LPS-induced NO production dose-dependently with IC50 value of 4.62 μM, 11.40 μM, 16.33 μM and 7.70 μM respectively and inhibited the reactive oxygen species (ROS) generation with IC50 value of 9.48 μM, 6.48 μM, 28.16 μM and 12.86 μM respectively. These attenuations were believed to be the result of the perturbation of the inducible nitric oxide synthase (iNOS) enzyme expression in RAW264.7 cells. The data also suggested that all four compounds exhibited anti-inflammatory properties by selectively attenuating COX-2 activation, thus inhibiting the production of prostaglandin E2 (PGE2) with IC50 value of 10.31 μM, 26.18 μM, 10.32 μM and 36.20 μM respectively in human whole blood cells. On the other hand, the ratio of IC50 of COX-2/COX-1, which are associated with the production of thromboxane B2 (TxB2) in caprine whole blood cells, demonstrated that flavokawain B (ratio; 0.24 ± 0.08) was the most selective towards the COX-2 enzyme, followed by atrovirinone (ratio; 0.32 ± 0.09), cardamonin (ratio; 0.42 ± 0.07) and zerumbone (ratio; 0.72 ± 0.17). Interestingly, three of the compounds, namely atrovirinone, cardamonin and zerumbone, have a dual COX/LOX inhibitory activity. In addition, cardamonin,flavokawain B and zerumbone showed significant inhibition on the synthesis of TNF-α, IL-1β, IL-6 and IL-10 in RAW 264.7 cells in a dose-dependent manner. In contrast, atrovirinone significantly reduced the synthesis of pro-inflammatory cytokines, namely TNF-α, IL-1β and IL-6 while it increased the secretion of the anti-inflammatory cytokine, IL-10. It is interesting to note that all four compounds suppressed the phosphorylation of the mitogen-activated protein kinases (MAPKs), namely extracellular signal-regulated protein kinases 1 and 2 (ERK1/2) and p38 MAPK. Furthermore, it was hypothesized that the unique chemical structures of these phytochemicals are the main cause for their varying degrees in anti-inflammatory activities. In this study, two chalcone derivatives, namely cardamonin and flavokawain B were tested. The results demonstrated that substitution on the B ring was not essential for the anti-inflammatory activity of these chalcones. Besides, the presence of one or more hydroxylated and methoxylated benzoyl ring in the chalcones might enhance their scavenging and lipophilicity activities respectively. Similarly, it was suggested that the prenylated benzoquinone skeleton in atrovirinone might be important for its anti-inflammatory effect, which is due to the fact that compounds with prenylated chemical entities as part of their backbone structure are usually more hydrophobic than the non-prenylated compounds for easy penetration into the cell membrane. While in zerumbone, the α,β–unsaturated carbonyl group moiety might be important for its anti-inflammatory and antioxidant effect, which could induce the detoxification enzymes and neutralize the lipid peroxidation. In conclusion, these findings have shown that the inhibition of main inflammatory mediators production in the cellular models of inflammation might be due to the attenuation of the ERK1/2 and p38 signaling pathways. Thus, this study has demonstrated that atrovirinone, cardamonin, flavokawain B, and zerumbone are potential lead compounds for the discovery of a new generation of drugs for controlling various acute and chronic inflammatory diseases.